SMART TEACHING: PENERAPAN KECERDASAN BUATAN UNTUK MENDUKUNG EFEKTIVITAS PENGAJARAN - Tjahjono, Laura Mahendratta; Sword, Felicia; Nugraha, Satria Adi; Jodhinata, Andreas (CV. Kalimasada Group, 2025)
This research aims to explore the use of artificial intelligence (AI) in supporting teaching effectiveness and easing teachers' workload through the Smart Teaching: AI Solutions to Ease the Burden of Teachers training program. This activity was carried out in the form of a webinar organized by Ciputra University (UC) Informatics Online on January 23, 2025. The research method used is a qualitative descriptive study with an applied experiment approach, where webinar participants are introduced to various AI tools and directly practice their use in making lesson plans and developing AI-based teaching materials. The results showed a significant improvement in participants' understanding and skills related to the application of AI in teaching. A total of 92% of participants reported that they felt more prepared to integrate AI in the learning process, while 87% stated that the material provided was very relevant and applicable. The publication of research results is carried out through national journals with ISSN and mass media to expand the impact of this program. Additional outputs from this study include copyright-related training modules as evidence of innovative contributions in technology-based education. This study confirms that the use of AI in teaching can be an effective solution in easing the burden on teachers while improving the quality of education. Therefore, the sustainable development of AI-based training programs is recommended to support digital transformation in the world of education.